An observation of the versions of the long-song “Saruul tal”: (On the example of singing by two famous singers) - Dai, Tsatsral; Tseren, Chuluuntsetseg (Mongolian Journal of Arts and Culture, 2023)
The Mongolian long-songs are popular among the Mongolian nationalities. But the local long-song singing techniques and special features are distinctive. There are many long-songs with the same name which are differently sung in Mongolia and Inner Mongolia. For example, the song “SaruulTal” has been distributed in many versions in Mongolia and Inner Mongolia. We aimed to determine their singing special features, comparing the bargu version of the song “Saruul Tal”, sung by the famous Inner Mongolian singer N.Buyandelger with the version of the same song, sung by the famous Mongolian singer N.Norovbanzad. “Саруул тал” дууны хувилбарт хийсэн ажиглалт (Хоёр алдарт уртын дуучны дуулсан жишээн дээр) Хураангуй: Монгол урт ын дуу нь монгол туургатны хэмжээнд тархсан байдаг. Гэвч нутаг нутгийн уртын дуу дуулах арга барил, орон нутгийн өвөрмөц байдал нь өөр өөрийн онцлогийг хадгалж байдаг. Монгол улсад болон Өвөр Монголд өөр аяар дуулагддаг , адилхан нэртэй уртын дуунууд нэлээд олон байдаг. Тухайл бал , “Саруул тал ” дуу нь олон хувилбараар Монгол улсад болон Өвөр Монголд тархсан байдаг. Өвөр Монгол ын алдарт урт ын дуучин Н.Буяндэлгэрийн Барга хувилбараар дуулсан “Саруул тал ” дууг авч үзэхээс гадна Монгол улсын алдарт уртын дуучин Н.Норовбанзадын дуулсан “Саруул тал ” дууны хувилбартай жишин харьцуулж, улмаар хоёр алдарт уртын дуучны дуулах онцлог шинжийг тодорхойлохыг зорилоо . Түлхүүр үг: Н.Буяндэлгэр, Н.Норовбанзад, дуулах онцлог, барга